THU0267 THE SLE DISEASE ACTIVITY SCORE (SLE-DAS) ENABLES ACCURATE DEFINITIONS OF SLE REMISSION AND LDA AS ACHIEVABLE TARGETS IN DISEASE MANAGEMENT. (June 2019) - Jesus, Diogo; Matos, Ana; Henriques, Carla; Zen, Margherita; Larosa, Maddalena; Iaccarino, Luca; Doria, Andrea; Inês, Luís
Abstract : Background: The treat-to-target strategy in Systemic Lupus Erythematosus (SLE) aims to achieve remission. However, to define a target based on the SLE Disease Activity Index (SLEDAI) is questionable, due to its limitations (especially its dichotomous nature). The SLE Disease Activity Score (SLE-DAS) is a recently validated continuous disease activity score which has a higher accuracy in measuring SLE activity and a higher sensitivity-to-change compared to SLEDAI. 1 Objectives: To assess the ability of SLE-DAS to define SLE remission and other disease activity states. Methods: Cross-sectional study of SLE patients fulfilling the ACR'97 and/or SLICC'12 classification criteria and followed at the Padua Lupus Clinic from March to June 2018. At each outpatient visit, the attending clinician scored SLE disease activity (in the last 30 days) using Physician Global Assessment (PGA) (0-3 points, 10 cm scale), SLEDAI-2K and SLE-DAS. A senior rheumatologist expert in SLE, blinded to the disease activity scores, classified each patient in 1 of 4 categories: (i) remission, (ii) low disease activity (LDA), (iii) mild disease activity and (iv) moderate/severe disease activity. The best cut-off values of SLE-DAS to define these categories were estimated using Receiver Operating Characteristic (ROC) curve analysis. Accuracy, precision, sensitivity and specificity values for these cut-off values were then calculated. The agreement between the SLE-DAS and physician's classification was measured using Kappa coefficient. Statistical significance was set at 0.05. Results: We included 221 patients (84.2% female, mean age of 45.4±13.5 years, mean disease duration of 15.4±9.5 years). In this preliminary study, the proposed cut-off values of SLE-DAS to define each disease activity category were: remission SLE-DAS≤2.08, LDA 2.08<SLE-DAS≤3.77, mild disease activity 3.77<SLE-DAS≤7.64, and moderate/severe disease activity SLE-DAS>7.64 for (Table 1 ). The overall accuracy of these SLE-DAS cut-off values to identify each disease activity state was 96.4%. The agreement between SLE-DAS and physician's classification was very high (k=0.925, p<0.001). Distribution of SLE-DAS and SLEDAI-2K scores in each disease activity state is presented in Figure 1 . According to the SLE-DAS cut-offs, 68.8% of the patients were in remission, 2.3% in LDA, 10.9% in mild disease activity and 18.1% in moderate/severe disease activity. Conclusion: The SLE-DAS has a high precision in identifying remission, LDA, and other disease activity states in SLE. These results suggest that the SLE-DAS is an accurate tool in defining achievable targets in SLE management. References: [1] Jesus D, Matos A, Henriques C, et al. Derivation and validation of the SLE Disease Activity Score (SLE-DAS): a new SLE continuous measure with high sensitivity for changes in disease activity. Ann Rheum Dis 2019, Epub ahead of print 9 January 2019. DOI: 10.1136/annrheumdis-2018-214502. Disclosure of Interests: None declared